PENGARUH STRESS DAN DISIPLIN TERHADAP PRODUKTIVITAS KERJA KARYAWAN SUPPORTING PADA PT. INDAH KIAT PULP AND PAPER TBK DI PERAWANG - Alies Kharisma Putri; Jumiati Sasmita; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research carried qut on a beautiful PT. Indah Kiat Pulp & Paper Tbk in Perawang. The study aims to determine how the influence of stress and discipline simultananeously or partial on employee produktivity PT Indah Kiat Pulp & Paper Tbk supporting the wonderful in Perawang. As for the population in the study are the employees who work in a beautiful PT Indah Kiat Pulp & Paper Tbk in Perawang which amounted to 51 people. The analysis is descritive analysis. As it also uses multiple linear regression method with the help of SPSS (Statistical Package of Social Science) version 20.The results of tests performed simultaneous regression test or test f indicates that stress and discipline significant effect on employee productivity supporting. Partial test results t test results showed that the stress variables partially significant effect on employee productifity supporting. And variable discipline partially significant effect on productivity. Of the independent variables is known that stress has a dominant influence on employee productivity supporting.Keywords: Stress, Discipline, and Employee Productivity.